Features of pregnancy course in patients with thrombophilia and abnormal placenta location - V. B. Zubenko; A. I. Lovkova (Акушерство, гинекология и репродукция, 2023)
Aim: to identify inherited and acquired thrombophilia as well as features of pregnancy course in women with abnormal placenta location.Materials and Methods. Within the framework of a prospective controlled cohort non-randomized, interventional study there was analyzed pregnancy course in 135 women with abnormal placenta location: group I – 42 patients with abnormal placenta location in history; group II – 61 women with placenta previa detected during ongoing pregnancy; group III – 32 patients with placenta previa detected both in ongoing and previous pregnancy. The control group consisted of 120 pregnant women with normal placenta location without a previous complicated obstetric history. All patients underwent clinical examination of pregnancy course assessing fetus intrauterine growth retardation (IUGR) and fetal biophysical profile; inherited and acquired thrombophilia were identified – analyzing circulating antiphospholipid antibodies (APAs) by ELISA, inherited thrombophilia by polymerase chain reaction to identify mutations in genes encoding 5,10methylenetetrahydrofolate reductase (MTHFR), G20210A mutations in prothrombin gene, V Leiden mutation, polymorphismin fibrinogen and plasminogen activator inhibitor 1 (PAI-1) genes.Results. Inherited thrombophilia was detected in 101 (74.81 %) pregnant woman with abnormal placenta location: group I – in 31 (73.8 %) patients, group II and group III – in 44 (72.1 %) and 26 (81.3 %) patients, respectively. Inherited forms of thrombophilia were detected in 29 (24.2 %) women from control group. Multigenic forms of thrombophilia peaked in group III (14/43.8 %), followed by group I (16/38.1 %) and group II (23/37.7 %). In the control group, multigenic thrombophilia was detected in 16 (13.3 %) women. Selective inherited thrombophilia and АРАs circulation were detected in 30 (22.22 %) women with abnormal placenta location: group I – in 8 (19.0 %) patients, group II – in 13 (21.3 %), and group III – in 9 (28.1 %) cases. In the control group, there were only 8 (6.7 %) such patients. Patients with IUGR signs were identified in all study groups: 4 (9.52 %) in group I, 6 (9.84 %) in group II, 6 (18.75 %) in group III as well as in control group in 6 (6.67 %) women.Conclusion. Pregnancy management in patients with thrombophilia and placental abnormalities should be accompanied by an proper fetal assessment (biophysical profile) and, in some cases, anticoagulant or antiplatelet therapy. However, insufficient number of cases requires to conduct further investigations to assess a relation between thrombophilia, placenta previa and a risk of obstetric complications particularly IUGR.